From Projects to Practice: Integrating PjBL and CTL to Elevate Vocational EFL Students’ Engagement - Gani, Amilia Sari; Ruminda, Ruminda; Bachtiar, Bachtiar (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study examines the effectiveness of integrating Project-Based Learning (PjBL) and Contextual Teaching and Learning (CTL) in enhancing students’ engagement in English learning at a vocational high school. A mixed-methods design was employed, involving questionnaires, classroom observations, and interviews with 33 students majoring in chemical analysis. Quantitative data were analyzed using descriptive statistics, while qualitative responses were thematically coded. The findings indicate that the integration of PjBL and CTL increased students’ engagement, confidence, and ability to apply English in real-world vocational tasks, such as laboratory procedures and technical reporting. Mean scores showed generally positive perceptions, while low standard deviations reflected consistent responses across participants. Qualitative evidence highlighted improvements in communication, collaboration, and critical thinking, with students reporting stronger motivation and preparedness for professional English use. This study contributes to vocational English pedagogy by providing empirical evidence of the complementary strengths of PjBL and CTL in bridging academic learning with workplace relevance. The proposed instructional framework offers practical guidance for educators in technical-vocational institutions, ensuring better alignment between language instruction and the demands of globalized industries.